The elimination effects of lavender essential oil on Listeria monocytogenes biofilms developed at different temperatures and the induction of VBNC state. (15th March 2022) - Han, X.; Chen, Q.; Zhang, X.; Peng, J.; Zhang, M.; Zhong, Q.
Abstract: Listeria monocytogenes is a typical foodborne pathogen that causes hard‐to‐treat bacterial infections, mainly due to its ability to form biofilm and enter into a viable but non‐culturable state (VBNC). In this study, we investigated the removal effects of four antimicrobial agents on L. monocytogenes biofilms formed at 32°C and 10°C, analysed the resistances of the mature biofilms to antimicrobial agents, and explored the VBNC state of cells in mature biofilms induced by lavender essential oil (LEO). The results showed that the growth of L. monocytogenes was completely inhibited when 1·6% (v/v) of the LEO was added. Meanwhile, the results of the crystal violet staining and XTT reduction method indicated that different concentrations of LEO significantly reduced L. monocytogenes biofilms biomass and metabolic activities, followed by sodium hypochlorite, lactic acid, and hydrogen peroxide. Moreover, the confocal laser scanning microscopy (CLSM) images confirmed that the treated biofilms became thinner, the structure was sparse, and the appearance was blurry. More interestingly, L . monocytogenes biofilms developed at 10°C were less susceptible to the sanitizers than those formed at 32°C. In addition, LEO presented a more significant dispersing effect on the biofilm cells, and 1/2 MIC to 4 MIC of LEO could induce fewer VBNC state cells in biofilm and plankton compared with sodium hypochlorite. This study indicated that the LEO could be considered as an ideal antibiofilm agent for controlling L. monocytogenes . But we should pay attention to the resistance of the biofilms developed at low temperatures. Abstract : Significance and Impact of this Study: The biofilm and viable but non‐culturable state (VBNC) of Listeria monocytogenes are regarded as potential harms to public health. It is of great significance to apply lavender essential oil (LEO) as an alternative of disinfectant and antibiotics to control the pathogenicity and drug resistance of pathogens enhanced by biofilms. This work mainly evaluated the elimination effects of LEO on L. monocytogenes biofilms formed at 32°C (warm biofilm) and 10°C (cold biofilm). The results presented that LEO exhibited effective eradicating effects on L. monocytogenes biofilms formed at different temperatures, significantly reduced the VBNC cell number in mature biofilms and promoted the dispersion of biofilm cells into plankton. Our findings support that LEO has the potential to be applied as an ideal antibiofilm agent to control the contamination and infection of L. monocytogenes .